Bentuk Fathering di Kota Kupang - Beatriks Novianti Bunga; Siti Nurasia; Herlina Clemens (Universitas Nusa Cendana, 2019)
Parents have responsibilities to nurture their children to be independent person, physically and biologically. Father’s role are parenting, demanding them to be involved in child rearing. This study was done for six months long in order to understand fathering practices in Kupang City using quantiative methods. Samples involved in this study numbered 200 fathers with children aged 2 – 6 years old in Kupang City. Sampling used was accidental sampling and data gathered with a 35 items questionnaire. These items were tried in validity and reliability. This study found that fathers involvement in parenting were as high as 83%. Paternal accessibility were identified as the most important fathering aspect. This study also describe the data according to important demographics information. This study needs to be further explored using qualitative approach in order to achieve better and deeper quality of information.